2018
DOI: 10.1111/nph.15481
|View full text |Cite
|
Sign up to set email alerts
|

Bark, the neglected tree postural motor system

Abstract: This article is a Commentary on Clair et al., 221: 209–217.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…2B-2D). The anatomical structure of bark in species with tensile stress is similar to that observed in Malvaceae species (Roth 1972;Kotina et al 2017;Clair et al 2019) or some extinct plants (Masselter et al 2017;Poppinga and Speck 2019), and here observed in various botanical families. Among these species we observed the presence of fibers with a G-layer in three cases (Carapa surinamensis, Supplementary data, Fig.…”
Section: Discussionsupporting
confidence: 83%
“…2B-2D). The anatomical structure of bark in species with tensile stress is similar to that observed in Malvaceae species (Roth 1972;Kotina et al 2017;Clair et al 2019) or some extinct plants (Masselter et al 2017;Poppinga and Speck 2019), and here observed in various botanical families. Among these species we observed the presence of fibers with a G-layer in three cases (Carapa surinamensis, Supplementary data, Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Rather, the stem is stabilised to a large degree by a fibre system within the secondary phloem (Fisher and Mueller 1983;Kempe et al 2014). These special fibre systems, fossil and recent, probably operate in quite the same manner like a "trellis" system (Poppinga and Speck 2019). There is ongoing progress in understanding plant stem constructions, and evidence was found recently that bark can also substantially contribute to mechanical behaviour in dicot trees (Clair et al 2019).…”
Section: The Tree-a Multifunctional Affairmentioning
confidence: 99%